Peran Dinas Pemuda Olahraga Kebudayaan dan Parawisata Kabupaten Mojokerto Dalam Pengembangan Petirtaan Jolotundo Di Kecamatan Trawas Kabupaten Mojokerto - Martini, Renanda Yulio Putri; Kusbandrijo, Bambang; Hartono, Supri (Sagita Academia Journal, 2025)
This research discusses the role of the Mojokerto Regency Youth, Sports, Culture and Tourism Office in the development of Petirtaan Jolotundo in Trawas District. The background of the research highlights the great potential of Mojokerto's cultural and historical tourism, particularly Petirtaan Jolotundo, which is an ancient site from the Airlangga era. The research method used a descriptive qualitative approach with observation, interviews, and documentation. The results show that the Dinas acts as a regulator, dynamizer, facilitator, and catalyst through policy-making, training, provision of facilities, and promotion. However, barriers include limited funding and community awareness. The research conclusion underlines the importance of sustainable strategies and cross-party cooperation to optimize Jolotundo's cultural tourism potential.